Generic NDC: Equilibrium, valuation and risk sharing with and without NDC bonds - Edward Palmer (Uppsala University, Department of Economics, 2011)
The Non-financial (Notional) Defined Contribution (NDC) PAYGO pension scheme is a recent innovation and its generic dimensions have not previously been explored in a coherent context. This paper does this. It derives and analyzes the demographic, economic and distributional properties of NDC. The residual (systematic) longevity risk creates a special problem, solved with an NDC bond, the asset that closes the system financially, transferring residual risk to the government (taxpayers). This guarantees a fixed NDC contribution rate and, thus, intergenerational commitment, with transparent distributional policy pursued through targeted transfers from general tax revenues and taxation of overall personal income.
urn:nbn:se:uu:diva-145481
Keywords: H55; I38; J14; O23; P16; 330; Pensions; NDC; Notional Defined Contribution; Non-financial Defined Contribution; NDC Bond; Risk sharing; Pension Policy; Pay-as-you-go; PAYG; Gesetzliche Rentenversicherung; Umlageverfahren; Rentenpolitik; Schweden